(untitled) (MMIT Proceedings, 2026)
This paper analyzes the attitudes of the students towards the use of artificial intelligence in Academic English and Study Skills lessons at Tashkent International University of Education (TIUE). The data were collected by means of a mixed-methods survey of 20 undergraduate students in the International Foundation Program for the academic year of 2025-2026. Based on the results, it can be concluded that there is a wide but conservative application of AI by undergraduates. Even though most respondents admitted their usage of generative AI chatbots in academia, students also raised issues related to plagiarism, dependence on AI tools, lack of originality, and potential negative impact on developing critical thinking skills. Based on the obtained results, the notion of "Efficiency–Integrity Paradox" can be introduced. In addition, the results show that undergraduates do not view AI as a means to replace human efforts with automation but rather use AI as a tool to support learning activities. Finally, the majority of the sample mentioned the necessity for universities to provide students with AI literacy training and develop academic guidelines. It is argued that universities should abandon prohibitive strategies for AI usage and implement AI literacy models.